Microglia modulate the cerebrovascular reactivity through ectonucleotidase CD39 - Zhongxiao Fu; Mallikarjunarao Ganesana; Philip Hwang; Xiao Tan; Melissa Marie Kinkaid; Yu-Yo Sun; Emily Bian; Aden Weybright; Hong-Ru Chen; Katia Sol-Church; Ukpong B. Eyo; Clare Pridans; et al. (Nature Communications)
Abstract Microglia and the border-associated macrophages contribute to the modulation of cerebral blood flow, but the mechanisms have remained uncertain. Here, we show that microglia regulate the cerebral blood flow baseline and the responses to whisker stimulation or intra-cisternal magna injection of adenosine triphosphate, but not intra-cisternal magna injection of adenosine in mice model. Notably, microglia repopulation corrects these cerebral blood flow anomalies. The microglial-dependent regulation of cerebral blood flow requires the adenosine triphosphate-sensing P2RY12 receptor and ectonucleotidase CD39 that initiates the dephosphorylation of extracellular adenosine triphosphate into adenosine in both male and female mice. Pharmacological inhibition or CX3CR1-CreER-mediated deletion of CD39 mimics the cerebral blood flow anomalies in microglia-deficient mice and reduces the upsurges of extracellular adenosine following whisker stimulation. Together, these results suggest that the microglial CD39-initiated breakdown of extracellular adenosine triphosphate co-transmitter is an important step in neurovascular coupling and the regulation of cerebrovascular reactivity.